DASAR PERTIMBANGAN HUKUM MAHKAMAH AGUNG RI TENTANG WASIAT WAJIBAH - Sidik Tono (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
Judgments of the Supreme Court RI relating to wasiat wajibah was many, especially in the last of 10 years. In this study, researchers focused on the legal considerations of the Supreme Court relating to wasiat wajibah that finally being jurisprudence. This study aims to provide an explanation of legal consideration basic used in the decisions of the Supreme Court in the case of wasiat wajibah. This study examines the consistency of legal consideration used by Supreme Court in the similar case, especially in the duration 2006-2013.